The Toyota product development system : integrating people, process, and technology - Morgan, James M.; Liker, Jeffrey K. (Productivity Press, 2006)
The ability to bring new and innovative products to market rapidly is the prime critical competence for any successful consumer-driven company. This book examines and analyzes the truly effective product development methodology that has made Toyota the most forward-thinking company in the automotive industry